Level of knowledge in prevention of oral health in pregnant women treated in two national peruvian hospitals - Sotomayor Camayo, Justiniano (2012)
The purpose of this study was to determine the level of knowledge on prevention in oral health in pregnant women attending the Obstetrics and Gynecology Service of the Hipolito Unanue Nacional Hospital and San Jose Hospital-2011. We performed a prospective descriptive study, and Cross, in 249 pregnant women attending the Obstetrics and Gynecology Service of the Hipolito Unanue Hospital and 158 patients who came to San Jose Hospital (2011). A questionnaire was administered to measure the level of knowledge about preventive oral health, oral disease and the relationship between dental care and pregnancy. 84 % of all pregnant women surveyed reported no dental care. Only 14 % have knowledge about oral hygiene items, and less than 50 % have knowledge about nutrition during pregnancy and its effect on the child’s teeth. 64 % have a good level of knowledge about preventive measures, however, about oral diseases and pregnancy in relation to dental care is the level of knowledge is bad, so the level of general knowledge among pregnant women on prevention measures oral health is bad.